Study on the Influence of Grooving Parameters of Lapping Gear Vibration System on Vibration Characteristics - Derong Zhu; Na Li; Hao Li; Jianjun Yang; Xiaozhong Deng; Hongmin Xin; Fuquan Nie (Jixie chuandong)
In the field of precision processing technology of spiral bevel gears， the processing technology of ultrasonic lapping gears has been closely followed and studied by many scholars. A vibration system of ultrasonic lapping gear is designed. Under the same conditions concerning the attribute settings， grid partition， and modal analysis settings of the material， the influences of the number， width， length and position on the resonance frequency， vibration mode， displacement node and gear deformation are analyzed by Ansys Workbench； a method for controlling the coupled vibration produced by grooving the transmitted cylinder is established， which can further enrich and improve the existing design theory of the processing vibration system for ultrasonic lapping gears.